Unusual adenomatoid odontogenic tumor - Oliveira, Marina Reis [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Gabrielli, Mario Francisco Real [UNESP]; De Andrade, Cleverton Roberto [UNESP]; Silva, Breno Nogueira; Pereira-Filho, Valfrido Antonio [UNESP] (Wolters Kluwer, 2016)
The adenomatoid odontogenic tumor is a rare benign neoplasm. It can, however, have locally aggressive behavior. This is a case of an adenomatoid odontogenic tumor of unusual location and behavior in a 15-year-old female patient. A panoramic radiograph revealed a large radiolucent lesion involving the retained tooth 33. Teeth involved in this lesion were displaced and with apparent root resorption. A prototype of the mandible showed a marked expansion of cortical bone, fenestration points in the lingual cortex, and fragility of the base of the mandible. Therefore, because of the risk of postoperative pathologic fracture the placement of a 2.4-mm reconstruction plate was indicated. Total enucleation of the lesion, as well as placement of a reconstruction plate were performed. Despite the large bone destruction, with the correct surgical procedure and the use of the reconstruction plate the patient recovered without incidents and a 24-month postoperative radiography showed satisfactory bone formation.
Keywords: Adenomatoid odontogenic tumor; Bone regeneration; Reconstruction plate; Root resorption